(untitled) (Jurnal Pilar Nusa Mandiri, 2021)
This research has aim to produce for detection system of human ten fringerprints patterns that according to Dermatoglypic. The fringerprints patterns able to use for advanced analysis to biological and psychological characteristics. This research use back propagation algorithm of neural network to identify of fringerprint patterns. Initial processing is used mathematical morphology method before it is detected. The image is changed to digital image and then it is processed by dilation and erotion for enhancement image. The image that as neuron input of back propagation is changed to gray scale and 8 x 8 of size. Training process use 2000 epochs and patterns [200 2 1]. The output result are identification of human ten fringerprints patterns. This research produce identification are whorl, arch, right loop and left loop patterns of fringerprints. The result of research are whorl patterns 51.67%, right loop patterns 23.33% and left loop 18.33%. The accuration of detection system is 93.33%.